2011
DOI: 10.1038/ijir.2011.46
|View full text |Cite
|
Sign up to set email alerts
|

Is there a concordance between carotid and penile cavernosal artery intima-media thickness in patients with erectile dysfunction?

Abstract: This study aimed to investigate the predictive accuracy of carotid and cavernosal Doppler ultrasound findings for discriminating patients with vasculogenic erectile dysfunction (ED). Fifty patients with complaints of ED were included. B-mode ultrasound of bilateral carotid arteries were performed and peak systolic velocity (PSV), end-diastolic velocity (EDV) and intima-media thickness (IMT) values were measured. Afterwards, corresponding values of cavernosal arteries were obtained by penile color duplex ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…When patients were reclassified according to carotid IMT values (IMT of the first group < 0.9 mm and the second > = 0.9 mm), carotid PSV and EDV values were different (P = 0.033 and 0.018, respectively). Cavernosal PSV and EDV displayed no difference (P = 0.816 and 0.123) while cavernosal IMT and percent change of cavernosal caliper were significantly different (P = 0.014 and 0.018) (46). Caretta performed a high magnification ultrasonographic study in order to compare functional and morphological parameters of the cavernous artery to PSV and their relation with penile and systemic atherosclerosis (47).…”
Section: Discussionmentioning
confidence: 99%
“…When patients were reclassified according to carotid IMT values (IMT of the first group < 0.9 mm and the second > = 0.9 mm), carotid PSV and EDV values were different (P = 0.033 and 0.018, respectively). Cavernosal PSV and EDV displayed no difference (P = 0.816 and 0.123) while cavernosal IMT and percent change of cavernosal caliper were significantly different (P = 0.014 and 0.018) (46). Caretta performed a high magnification ultrasonographic study in order to compare functional and morphological parameters of the cavernous artery to PSV and their relation with penile and systemic atherosclerosis (47).…”
Section: Discussionmentioning
confidence: 99%
“…Egy munkacsoport a MSval társult ED-ban szenvedők 70,3%-ában igazolta a pénisz cavernosus artériájának csökkent véráramlását és 59,3%-ukban a szisztémás érrendszer kóros állapotát [36]. Más kutatók is megállapították Doppler-ultrahangvizsgálattal, hogy az ED-ban szenvedő férfiak felében az ED vascularis eredetű [37]. Ezekben a betegekben a pénisz cavernosus artériájának fala megvastagodott, és egyúttal a nyaki artériában is kimutatható volt a véráramlás csökkenése.…”
Section: Férfiakban Előforduló Szexuális Funkciózavarunclassified
“…Men with vascular erectile dysfunction have higher carotid intimaemedia thicknesses than individuals with erectile dysfunction of other causes or healthy controls. 54,55 In this context, carotid intimaemedia thickness has been proposed as a tool for the further risk assessment of patients with vascular erectile dysfunction who are considered at intermediate risk. 30,33 Nevertheless, studies have shown that the prognostic value of carotid intimaemedia thickness beyond traditional risk factors in the general population is modest, 56 and the 2013 American College of Cardiology/American Heart Association risk assessment guideline recommends against "measuring carotid intima-media thickness in routine clinical practice for risk assessment for a first atherosclerotic cardiovascular disease event" 28 (class III, level B).…”
Section: Carotid Ultrasound Imagingmentioning
confidence: 99%